A Systematic Literature Review on Tax Evasion: Insights and Future Research Agenda - Nivakan, Sritharan; Salawati, Sahari; Cheuk, Sharon Choy Sheung (Human Resource Management Academic Research Society, 2022)
Emerging research studies in the subject of tax evasion have selected a variety of factors to verify their influence on the intentional non-compliance behaviour (tax evasion). However, a holistic review of tax evasion covering global literatures remains elusive. Therefore, this paper intends to conduct a systematic literature review (SLR) to review the existing articles in the past 10 years, encapsulating 100 papers starting from 2010, in which Organisation for Economic Co-operation Development (OECD) established the Convention on Mutual Administrative Assistance in Tax Matters in order to reduce tax evasion with the help of collaborated network. The review articulates those existing studies have limited their exploration within individual and economic related factors, but less focused on the other variables such as digitalization of public services, corporate social responsibility, and whistleblowing efforts. This paper also exhibits the avenues for future researchers in the subject of tax evasion.